Kearifan tempatan dan potensinya sebagai tarikan pelancongan berasaskan komuniti: Kajian kes komuniti Bajau Ubian di Pulau Mantanani, Sabah (Local knowledge and its potential as a community-based tourism attraction: The case of the Bajau Ubian Community in Mantanani Island, Sabah) - Mohd Jirey Kumalah; Gusni Saat; Jabil Mapjabil; Rosazman Hussin; Teuku Afrizal; Mustapa Abu Talip (Penerbit UKM, 2015)
Community-based tourism is a type of tourism which seeks to achieve sustainable development of rural communities whereby their standard of living can be improved without jeopardising environmental integrity. Sabah is one of the states in Malaysia that is well-endowed with tourism attractions based on culture and environment. This state has more than thirty ethnic tribes that are rich in native art and distinctive local knowledge and culture among which is the Bajau Ubian tribe of the scenic Mantanani Island. This study found six classifications of local knowledge that could be turned into tourist attractions, namely, cuisine, handicrafts and carpentry, traditional games, life skills, several arts of dance and music, and festival celebrations. Each of these local knowledge had the potential to become a community-based tourist attraction for the Mantanani Island.